(untitled) (Philadelphia, Pennsylvania, 1992)
The book is organized into five sections. Section 1 covers basic surgical anatomy of the orbit and clinical preoperative considerations. Section 2 covers surgical approaches to the orbit. Section 3 is devoted to the orbital surgery for Graves' diseases. Section 4 reviews the management of orbital trauma with emphasis on orbital fracture repair and foreign body removal. Section 5 covers surgical management of orbital diseases. The descriptions, photographs, and radiologic images, are included in these chapters to serve illustrative examples and as a helpful review for the readers
Keywords: eye-sockets,orbit,orbital diseases; surgery,atleses,surgery,atlases,surgery,atlases